Thrips palmi Karny (Thysanoptera Thripidae) could it survive in New Zealand - Dentener, P.R.; Whiting, D.C.; Connolly, P.G. (New Zealand Plant Protection, 2002)
Melon thrips (Thrips palmi Karny) is one of several Risk Group 2 pests on New Zealand MAF Biosecurity Authoritys list of unwanted pests Its wide host plant range and its presence worldwide including several countries in the Pacific region underpin its biosecurity status In this case study we used CLIMEX a climate matching software program to determine likely locations in New Zealand where melon thrips could establish once introduced Possible establishment was based on climate match with overseas locations where melon thrips is present and on a range of biological parameters specific to the response of melon thrips to climatic conditions The upper North Island is predicted to be most suited to melon thrips establishment This also matches the known New Zealand distribution of Hercinothrips bicinctus banana thrips a species found worldwide in locations similar to that of melon thrips